Massa e minorias, uma única Igreja - Melo, Antônio Alves de (Revista eclesiástica brasileira, 2000)
Must the Church be open to the masses or welcome only minori- ties? This question inspires the present article. In oíder to answer it, the Autor addresses a series of subjects: masses and minorities as components of human condition; the welcome, the space and the historical understandingfor the Church membership of masses and minorities; the relativity of the difference between the heroe, the saint, the genius and ordinary people; the rootedness of this relativity in the universal call to holiness. From the Church membership of the masses and minorities arises the image of a Church made up of concentric circles that move irregularly in relation to the center, which is Jesus Christ present in the Holy Spirit. Church membership happens through many different forms; and this challenges the pastoral work to a greater resilience and a greater creativity, so that masses and minorities be attained by this work. The pastoral of masses in Brazil requires particularly an articulation between the networks of communities and popular catholicism.